Azole Resistance in Aspergillus fumigatus: A Consequence of Antifungal Use in Agriculture? - Berger, Sarah; El Chazli, Yassine; Babu, Ambrin F.; Coste, Alix T. (Frontiers in Microbiology, 2017)
Agricultural industry uses pesticides to optimise food production for the growing human population. A major issue for crops is fungal phytopathogens, which are treated mainly with azole fungicides. Azoles are also the main medical treatment in the management of Aspergillus diseases caused by ubiquitous fungi, such as Aspergillus fumigatus. However, epidemiological research demonstrated an increasing prevalence of azole-resistant strains in A. fumigatus. The main resistance mechanism is a combination of alterations in the gene cyp51A (TR34/L98H). Surprisingly, this mutation is not only found in patients receiving long-term azole therapy for chronic aspergillosis but also in azole naïve patients. This suggests an environmental route of resistance through the exposure of azole fungicides in agriculture. In this review, we report data from several studies that strongly suggest that agricultural azoles are responsible for medical treatment failure in azole-naïve patients in clinical settings.